Structure and diversity of fishes in a freshwater and coastal subtropical lagoon. Issue 4 (18th November 2016) - Ferreira, N. C.; Guereschi, R. M.; Machado, C.; Lopes, C. A.; Nuñer, A. P. O.
Abstract : This study examined the fish communities of Peri Lagoon in southern Brazil to aid in the development of an effective management plan because the area is under threat from human activities. Sampling of fish fauna, ichthyoplankton and limnological data were compared between sites, differing by habitat type and characteristics such as depth, substratum composition and vegetation type. Results were significantly related to site, with the highest diversity and abundance recorded at shallow vegetated sites. A total of 14 fish species were recorded throughout the lagoon, with the most abundant being Hyphessobrycon luetkenii . Of the 14 species, half were sampled at their larval stage, suggesting a healthy and protected system. Significantly more larvae and eggs were collected during colder months (autumn to winter) and at sites closer to stream flow, possibly owing to increased food sources and habitat protection. This study highlights the importance of Peri Lagoon as a nursery ground for a wide range of fish species, providing essential information for incorporation into the future protection of fish stocks throughout Brazil.